2014
DOI: 10.1063/1.4903731
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric and impedance behaviours of surface-treated nano-crystalline diamond film electrodes

Abstract: The electrochemical performances of hydrogen- and oxygen-terminated nano-crystalline diamond film electrodes were investigated by cyclic voltammetry and AC impedance spectroscopy. In addition, the surface morphologies, phase structures, and chemical states of the two diamond films were analysed by scanning probe microscopy, Raman spectroscopy, and X-ray photoelectron spectroscopy, respectively. The results indicated that the potential window is narrower for the hydrogen-terminated nano-crystalline diamond film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…On the other hand, sliding‐type interface is normally achieved by detecting the sliding motion with pressure/tactile sensor array or strip/grating electrodes along the trace . A 9 × 9 sensor array with separated electrodes is developed to achieve real‐time detection of contact position, trajectory, velocity, and acceleration of a sliding object .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sliding‐type interface is normally achieved by detecting the sliding motion with pressure/tactile sensor array or strip/grating electrodes along the trace . A 9 × 9 sensor array with separated electrodes is developed to achieve real‐time detection of contact position, trajectory, velocity, and acceleration of a sliding object .…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, the great advancements in integrated circuits, wireless communication, and wearable electronics with low power consumption have thrown great demands on developing energy‐harvesting technologies in an ambient environment. Among the developed energy‐harvesting technologies, piezoelectric energy harvesters, which convert ubiquitous and versatile kinetic energy in an ambient environment into electrical energy, have gained most attention due to their high energy‐conversion efficiency, material diversity, good scalability, and simple architectures . Inorganic piezoelectric crystals and ceramics, such as ZnO, Pb[Zr x Ti 1– x ]O 3 , and BaTiO 3 , have been widely used to fabricate piezoelectric nanogenerators (PNGs) with good performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the geometry of piezoelectric materials also significantly affected the performance of the corresponding piezoelectric energy harvesters, besides their dielectric constant and piezoelectric coefficient . Structural design is one of the important parts of wearable flexible devices as well .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Also, the design of a telemetry system based on wireless power transmission for physiological parameters monitoring is proposed. 24 Three papers are shown in Nano materials field, two of which are focused on diamond film: voltammetric and impedance behaviors of surface-treated Nano-crystalline diamond film electrodes 25 and the effects of hydrogen atoms on surface conductivity of diamond film. 26 In addition, copper Nano-clusters prepared by one-step electrodeposition is reported to be applied on nitrate sensing.…”
mentioning
confidence: 99%